Medical students` health-related quality of life – A comparative study - Latas, Milan; Stojković, Tihomir; Ralić, Tijana; Jovanović, Svetlana; Špirić, Željko; Milovanović, Srđan (Vojnosanitetski pregled, 2014)
Background/Aim. Previous studies on medical students’ subjective perception of health and health-related quality of life (HRQoL) showed inconclusive results. Moreover, there are no published studies to compare HRQoL of medical students to non-medical university students. The aim of the study was to assess subjective perception of health-related quality of life (HRQoL) in medical students’ sample, to compare it with non-medical university stu-dents and to ascertain predictors of better perception of HRQoL in medical students. Methods. Scores of all domains on the Mental and Physical Component Summary subscales and total score of the Short Form Health Survey (SF-36), used for assessment of HRQoL in samples of 561 medical and 332 non-medical university students were assessed and compared. In addition, linear regression to identify predictors of better perception of mental and physical components of HRQoL and overall HRQoL in the sample of medical students was used. The dependant variables were subscores and total score with the SF-36, and independent variables were certain sociodemographic and academic characteristics of the students. Results. Medical students had statistically significantly higher scores on the Mental Component Summary and total SF-36 score compared to non-medical students. Linear regression analysis demonstrated that higher scores of Physical Component Summary were associated with age, male sex and the year of studies. The Mental Component Summary were associated with age, male sex, the year of studies and marital status. The total SF-36 score was associated with age, male sex and the year of studies. Conclusion. Medical students perceive their health much better than other university students do, but female, older and second grade medical students have worse perception of their HRQoL. Those points should be potential target areas for specific prevention and treatment in order to achieve better HRQoL.